2000
DOI: 10.1121/1.428360
|View full text |Cite
|
Sign up to set email alerts
|

Rotating machinery dynamics simulation. I. Rigid systems with ball bearing nonlinearities and outer ring ovality under rotating unbalance excitation

Abstract: The radial clearance in rolling bearing systems, required to compensate for dimensional changes associated with thermal expansion of the various parts during operation, may cause dimensional attrition and comprise bearing life, if unloaded operation occurs and balls skid [D. Childs and D. Moyer, ASME J. Eng. Gas Turb. Power 107, 152-159 (1985)]. Also, it can cause jumps in the response to unbalance excitation. These undesirable effects may be eliminated by introducing two or more loops into one of the bearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…El-Sayed [28] used his experimental results that show radial stiffness of a DGBB under only a radial dead load to increase nonlinearly as load increases and derived an emperical equation for stiffness calculation. El-Saeidy [30] showed that an increase in the rotating unbalance load of a rigid rotor-ideal ball bearings system will shift its frequencies other than forcing (unbalance) frequency to a higher frequency region; i.e. system's nonlinearity is of the hard spring type.…”
Section: The Rolling Element Bearing Stiffness Matrixmentioning
confidence: 99%
See 2 more Smart Citations
“…El-Sayed [28] used his experimental results that show radial stiffness of a DGBB under only a radial dead load to increase nonlinearly as load increases and derived an emperical equation for stiffness calculation. El-Saeidy [30] showed that an increase in the rotating unbalance load of a rigid rotor-ideal ball bearings system will shift its frequencies other than forcing (unbalance) frequency to a higher frequency region; i.e. system's nonlinearity is of the hard spring type.…”
Section: The Rolling Element Bearing Stiffness Matrixmentioning
confidence: 99%
“…The works [1][2][3][4][5][6][7][8][9]15,[17][18][19][21][22][23][24][25][26][27][28][29][30][32][33][34][35][36][38][39][40][41][42][43][44]48,[50][51][52] use summation over the bearing rolling elements in contact to compute bearing total loads. Houpert [10,11] replaced this summation by integration using Sjovall's [12] axial and radial load distribution integrals (J a , J r ).…”
Section: The Rolling Element Bearing Stiffness Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Components of the vector 1 in the abc frame are (see El-Saeidy (1998, 2000a1 see also the derivation of 1 components in terms of Euler angles by, for example, El-Saeidy (1998)):…”
Section: Analytical Modelmentioning
confidence: 99%
“…The parameters affecting the natural frequency of the system are found to be not very easily identi ed by different researchers [20,21]. Akturk et al [4] showed that increasing the preload would force the system to oscillate with a higher stiffness bearing, and therefore the natural frequency of the system would be increased.…”
mentioning
confidence: 99%